2019
DOI: 10.1055/a-0858-2169
|View full text |Cite
|
Sign up to set email alerts
|

Fully covered self-expanding metal stents for refractory pancreatic duct strictures in symptomatic chronic pancreatitis, US experience

Abstract: Background and study aims  Fully covered self-expanding metal stents (FCSEMS) have been used to treat refractory pancreatic duct strictures. We aimed to evaluate the feasibility, safety, and efficacy of FCSEMS in chronic pancreatitis with refractory pancreatic duct strictures. Patients and methods  This was a retrospective multicenter cases series of patients who underwent endoscopic retrograde cholangiopancreatography (ERCP) with FCSEMS placement in the main pancreatic duct (MPD) at five tertiary care center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…In this case series, we demonstrate the potential efficacy of holmium or thulium laser therapy in treating refractory strictures. With regard to pancreatic duct strictures, the use of fully-covered metal stents may provide an effective long-term option, but in addition to cost, are subject to serious AEs including stent migration, stent-induced and non-traversable de novo strictures, and obstruction of the PD side branches, which may result in pancreatic sepsis [12,13]. Furthermore, catheter access across the stenosis is required for dilation and placement of plastic or metal stents.…”
Section: Discussionmentioning
confidence: 99%
“…In this case series, we demonstrate the potential efficacy of holmium or thulium laser therapy in treating refractory strictures. With regard to pancreatic duct strictures, the use of fully-covered metal stents may provide an effective long-term option, but in addition to cost, are subject to serious AEs including stent migration, stent-induced and non-traversable de novo strictures, and obstruction of the PD side branches, which may result in pancreatic sepsis [12,13]. Furthermore, catheter access across the stenosis is required for dilation and placement of plastic or metal stents.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with MPD strictures that remained symptomatic after a single plastic stent who were treated with a 6 mm or 8 mm Niti-S Bumpt Stent (Taewoong Medical, Gimpo-SI, South Korea), 89% of patients were asymptomatic after 3 years. Given the technical success of FCSEMS[ 80 ] and relative safety[ 81 , 82 ], larger studies with long-term data will be performed. An ongoing trial will look at the degree of pain reduction, SAE, and stricture resolution[ 83 ] in patients who received a FCSEMS.…”
Section: Pancreatic Disease: Pancreatic Stones and Pancreatic Leaksmentioning
confidence: 99%
“…4 Within this context, several groups have evaluated the use of fully covered selfexpanding metal stents as a salvage maneuver for these strictures. [5][6][7] Although currently available metal stents are designed for biliary indications, limited case series have found high success rates for pancreatic strictures but with the important caveat that randomized studies have not been performed for refractory pancreatic duct strictures.…”
mentioning
confidence: 99%
“…As for the risk of blocking or "jailing" the side branches of the pancreatic duct, this remains a concern with fully covered metal stents; however, recent studies examining these stents in the pancreatic duct have reported low rates of postprocedure pancreatitis or pancreatic sepsis, which raises the question of what role side branch occlusion plays in pain pathogenesis. [5][6][7] Regardless, the short length of these stents minimizes the area of coverage, which may reduce the risk of side branch obstruction.…”
mentioning
confidence: 99%